The Limiting Quality Factor of Electrically Small Antennas Inscribed into a Cylinder and an Ellipsoid - S. V. Ballandovich; L. M. Liubina; A. Y. Odintzov; M. I. Sugak (Известия высших учебных заведений России: Радиоэлектроника)
The estimations of the bound of the quality factor for electrically small antennas inscribed in a cylinder and the triaxial ellipsoid are obtained. For antennas whose shape is far from spherical, the above estimation allows to refine the Chu-McLean limit.